Samoa : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This Selected Issues paper on Samoa reviews limitations to the existing framework of monetary policy, and suggests ways to improve its effectiveness. It examines current instruments at the disposal of the central bank to conduct monetary policy, before showing why monetary policy execution can be sometimes difficult. It also shows that such problems are not uncommon in economies with shallow financial markets. The paper also takes stock of developments since the early 1990s, and asks what major impediments to sustained private development remain.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet